2014
DOI: 10.1016/j.foodhyd.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the function of proteins on the rheological and quality properties of rice based gluten free muffins

Abstract: 8The incorporation of proteins has been long established in the bakery industry to obtain 9 enriched products, but they also take active part on the making process of sweet baked 10 goods. This study was focused on assessing the role of proteins on the rheology and 11 quality of wheat free muffins by using rice flour. Six rice based formulations were used:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
193
1
18

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(235 citation statements)
references
References 26 publications
23
193
1
18
Order By: Relevance
“…Cake batter formulated at low whey protein concentration of 10 % was more viscous in nature with lower ratios of G'/G'' and it gets more elastic or solid like towards higher protein concentration of 15 to 20 % with increased G' value. Although G' and G'' of both proteins increased with concentrations, tan δ decrease suggested that the solid-like property of batter increases (Matos et al 2014). The fact that G' and G'' increase could be simply due to the effect of the ) of a untreated egg and whey protein, and b ultrasound treated whey protein concentration of existing protein components.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Cake batter formulated at low whey protein concentration of 10 % was more viscous in nature with lower ratios of G'/G'' and it gets more elastic or solid like towards higher protein concentration of 15 to 20 % with increased G' value. Although G' and G'' of both proteins increased with concentrations, tan δ decrease suggested that the solid-like property of batter increases (Matos et al 2014). The fact that G' and G'' increase could be simply due to the effect of the ) of a untreated egg and whey protein, and b ultrasound treated whey protein concentration of existing protein components.…”
Section: Resultsmentioning
confidence: 95%
“…Ultrasound treatment on whey protein has increased the viscoelasticity of its formulated batter with decreased tan δ (Fig. 4b) reflecting an increase in the predominance of the elastic component (Matos et al 2014). Sonication has altered the structural property of protein, which induced physical changes on the batter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies an increase of specific volume and improvement of sensory quality were observed after an addition of pea protein, which was also accompanied by a decreased retrogradation (Miñarro et al 2012). Matos et al (2014) stated, that the addition of pea protein to gluten-free muffins makes them softer and more elastic. In these group of protein preparation a special attention should be paid to carob germ proteins.…”
Section: Research Highlightsmentioning
confidence: 80%
“…Produkty bezglutenowe na ogół odznaczają się niższą wartością odżywczą, wynikającą z mniejszej zawartości białka, włókna pokarmowego, witamin i soli mineralnych [12,27]. Brak glutenu w produktach piekarskich wpływa także na ich teksturę [8,15,24]. Poszukiwane są więc dodatki, które wpłyną zarówno na zwiększenie wartości odżywczej produktów bezglutenowych, jak również na ich objętość i teksturę.…”
unclassified